Mark Sullivan papers - Sullivan, Mark, 1874-1952.; Sullivan, Mark, 1874-1952.
Correspondence, writings, and other papers relating to Sullivan's career as a journalist and author. Subjects include the Conference on the Limitation of Armament held in Washington, D.C., 1921-1922; social and political affairs; highway and automobile safety; Sullivan's syndicated newspaper columns; and his wife, Marie Buchanan Sullivan. Includes manuscript and galley proofs of Sullivan's six-volume work, Our Times; the United States, 1900-1925 (1926-1935). Sullivan's correspondents include Bernard M. Baruch, Edward William Bok, William Edgar Borah, Calvin Coolidge, Warren G. Harding, Christopher Morley, Theodore Roosevelt, William H. Taft, Ida M. Tarbell, and Woodrow Wilson. Also includes letters received by Marie Buchanan Sullivan from William Jennings Bryan, Ethel Roosevelt Derby, Forence Kling Harding, and Edith Kermit Carow Roosevelt.
Journalist and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baruch, Bernard M. -- 1870-1965 -- Correspondence; Bok, Edward William, -- 1863-1930 -- Correspondence; Borah, William Edgar, -- 1865-1940 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Derby, Ethel Roosevelt -- Correspondence; Harding, Florence Kling, -- 1860-1924 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Morley, Christopher, -- 1890-1957 -- Correspondence; Roosevelt, Edith Kermit Carow, -- 1861-1948 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Sullivan, Marie Buchanan, -- -1940.; Sullivan, Marie Buchanan, -- -1940 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Tarbell, Ida M. -- 1857-1944 -- Correspondence; Disarmament; Newspapers -- Sections, columns, etc; Traffic safety; United States -- Politics and government -- 1901-1953.; United States -- Social life and customs -- 20th century; Authors; Journalists